Performance management system, an effective service delivery tool in the South African Post Office : a case of the North East Region - Khotsa, K. C.; Sebola, M. P. (International Conference on Public Administration and Development Alternatives (IPADA), 2020)
This paper argues that postal administrators around the globe utilise Performance Management System to measure their own performance in pursuance of good governance, standardisation and effective service delivery. In South Africa, statistics conclusively shows that postal service is continuously operating at a loss and in 2014 it operated on an overdraft of R250 Million and has recorded a net loss of more than R361 Million. For the South African Post Office to be profitable, it must develop strategies which will convert the undesirable state of affairs and become financially sustainable. It is against this background that Performance Management System should be used as an appropriate effective service delivery tool to measure performance by the South African Post Office. This paper is based on the study that was conducted in the South African Post office, North East Region. The primary objective of the study was to determine whether Performance Management System is an effective service delivery tool in the South African Post Office, North East region. The research method employed in the study was of both qualitative and quantitative approach. The majority of the respondents strongly agreed that Performance Management System is a trusted tool to measure performance. This paper concludes by providing suggestions towards improving Performance Management System in the South African Post Office, in the North East Region.
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Performance; Performance appraisal; Performance management; Service delivery; Goal setting in personnel management; Performance -- Management; Performance standards; Employees -- Rating of